An Analytical Study of “Kashif ul Haqaiq” - Rahman, Muhammad; Nusrat; Mehmood, Sajid (sourcecoder, 2022)
The real name of Imdad Imam Asar is Imdad Imam and Asar is a pseudonym. He was born on August 7, 1849 in Salarpur district of Patna. His father’s name was Syed Wahiduddin Bahadur. His ancestors migrated from Iran in the 17th century. First, they were natives of Newra. It was possible. So, Imam Athar’s education and training was completed in this environment, that he belonged to a scholarly and wealthy family. Kashif ul Haqaiq "Imad is an excellent example of Imam Asar’s practical criticism. This book was written around this time When Haali was putting the stigma of "Muqadma Sher o Shaeri", but it was not given the importance it deserves.